2014
DOI: 10.2478/hukin-2014-0120
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Speed Performance In Soccer by a Playing Position and a Sports Level Using a Laser System

Abstract: The purpose of this study was to determine the kinematic variables that identify the quality of velocity in soccer players at different competitive levels and playing positions. This study had two independent variables: 1) a competitive level (competitive and non-competitive players); and 2) a playing position, with four levels (central defenders, wide defenders/midfielders, central midfielders and forwards). Forty-two soccer players took part in a 30 m sprint-test, which was measured using a laser sensor-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
3
22
0
6
Order By: Relevance
“…Mendez-Villanueva et al [16] observed MSS values compatible with the above ones for wide defenders (30.2 km • h -1 ), but for all other positions, the results were higher: 35 km • h -1 for central defenders, 34.3 km • h -1 for wide midfielders, and 31.2 km • h -1 for central midfielders in elite youth soccer players. In amateur soccer players, Ferro et al [25] showed higher values for MSS in relation to this study for all playing positions (ranging from 31.4 to 33 km • h -1 ). On the other hand, the present study revealed superior results for MSS in comparison with Al Haddad et al [26], whose study, conducted among youth elite soccer players, demonstrated that defenders, midfielders, and forwards had a mean MSS near 28.7 km • h -1 and wide defenders and central defenders exhibited the mean value of 27.7 km • h -1 .…”
Section: Discussionsupporting
confidence: 58%
“…Mendez-Villanueva et al [16] observed MSS values compatible with the above ones for wide defenders (30.2 km • h -1 ), but for all other positions, the results were higher: 35 km • h -1 for central defenders, 34.3 km • h -1 for wide midfielders, and 31.2 km • h -1 for central midfielders in elite youth soccer players. In amateur soccer players, Ferro et al [25] showed higher values for MSS in relation to this study for all playing positions (ranging from 31.4 to 33 km • h -1 ). On the other hand, the present study revealed superior results for MSS in comparison with Al Haddad et al [26], whose study, conducted among youth elite soccer players, demonstrated that defenders, midfielders, and forwards had a mean MSS near 28.7 km • h -1 and wide defenders and central defenders exhibited the mean value of 27.7 km • h -1 .…”
Section: Discussionsupporting
confidence: 58%
“…The somatotype and the body composition can also influence an individual's performance in football [47]. Among the physical parameters, the sprint ability, especially combined with short periods of recovery [2,49], is one of the most important as it can discriminate football players into different levels [17,21,24,31]. Sprinting has been suggested as the most frequent action performed before a goal [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that athletic performance, specifically the physical attributes of each athlete in soccer, may be influenced by positional differences, level of play (Division I vs. II vs. III), and sex. 10,14,16,28,[32][33][34] This study only involved DII male's soccer players; thus, the present findings may not be generalizable to female soccer players or athletes in different divisions. Further, the focus of this study was to investigate pre-season performance testing only.…”
Section: Discussionmentioning
confidence: 99%